The Dark Side: Photosensitizer Prodrugs - Sara Sansaloni-Pastor; Jordan Bouilloux; Norbert Lange (MDPI AG, 2019)
Photodynamic therapy (PDT) and photodiagnosis (PD) are essential approaches in the field of biophotonics. Ideally, both modalities require the selective sensitization of the targeted disease in order to avoid undesired phenomena such as the destruction of healthy tissue, skin photosensitization, or mistaken diagnosis. To a large extent, the occurrence of these incidents can be attributed to “background” accumulation in non-target tissue. Therefore, an ideal photoactive compound should be optically silent in the absence of disease, but bright in its presence. Such requirements can be fulfilled using innovative prodrug strategies targeting disease-associated alterations. Here we will summarize the elaboration, characterization, and evaluation of approaches using polymeric photosensitizer prodrugs, nanoparticles, micelles, and porphysomes. Finally, we will discuss the use of 5-aminolevulinc acid and its derivatives that are selectively transformed in neoplastic cells into photoactive protoporphyrin IX.